Molecular Docking Study of Active Compounds in Amaranthus tricolor Leaves as High Mobility Group Box 1 (HMGB1) Inhibitor in Breast Cancer - Ardiana, Rachmawati; Khasanah, Dewi Uswatun; Permatasari, Diah; Adianingsih, Oktavia Rahayu (JSMARTech, 2020)
Breast cancer shows the proliferation of malignant epithelial cells that limit the ducts and lobes of the breast. If this process is not controlled, it will cause lumps that can then spread to other parts of the body and cause death. High-mobility group box protein 1 (HMGB1) has been reported to play roles in promoting cell survival of breast cancer cells. The inhibition of HMGB1 could be a reasonable target for the treatment of breast cancer. Amaranthus tricolor has been found could reduce the viability of breast cancer cells. In this study, we aim to predict the ability of the active compounds in Amaranthus tricolor leaves to inhibit the HMGB1 through molecular docking study. The molecular docking was conducted by using the PyRx software. This study shows that the four active compounds in Amaranthus tricolor leaves, namely isorhamnetin, routine, myricetin, and quercetin, have the smallest bond energy, indicating that the four compounds are the most stable and have the highest potency as HMGB1 inhibitor.